Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

Efficacy of micro-financing women's activities in Côte d'Ivoire: Evidence from rural areas and HIV/AIDS-affected women - Binaté Fofana, Namizata (Wageningen Academic Publishers, 2010)
This book deals with the effectiveness and the capability of microfinance institutions (MFIs) to enhance women's livelihoods and empowerment and to mitigate the effects of HIV and AIDS in Côte d'Ivoire. The results show that MFI credit causes positive and negative effects. MFI credit has improved incomes, the level of farm production and human and social capital. MFI credit has also enhanced women's decision-making power within households due to their new ability to contribute to the improvement of the household standard of living. Furthermore, women's empowerment regarding the demand for and the use of credit give them more opportunity to obtain MFI credit. Despite the positive effects of MFIs on women's income, this publication shows that loan repayment was not successful among some female borrowers due to the fact that the loan has not been used for investment purposes. For MFIs, the diversion of loans can endanger their functioning and sustainability and therefore their effectiveness in rural areas. Regarding HIV, this book highlights the diversity and the specificity of the way HIV-affected individuals are financially supported by credit institutions. Both the direct and indirect effects of HIV and AIDS on women's livelihood and MFIs are analysed.
Keywords: Infections transmisibles sexuellement et par le sang; OFDIG; VIH; afrique; côte d'ivoire; discipline; femmes*; finance; microfinance; régions géographiques; santé; sciences de la gestion; thématiques; économie